Penerapan dan Pengembangan Kurikulum Merdeka di PAUD Islam Makarima Kartasura Sukoharjo - Fauziyyah, Ulya; Putri Felani, Adelia Feby; Hanik Lutfiyah; Marda Ulya Reksadini (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The purpose of this study is to examine how PAUD Islam Makarima has developed and implemented the Merdeka Curriculum. This study's main goals are to investigate how this curriculum is used in the early childhood education setting and to determine how it affects learning outcomes. A qualitative technique is being used in the data collection process, which includes document analysis, observations, and interviews. To get a whole picture, the study includes management, parents, and teachers as participants. The results show that PAUD Islam Makarima's adoption of the Merdeka Curriculum has improved the adaptability and significance of the educational process. Parents saw improvements in their children's social and emotional development, while teachers reported an increase in the children's motivation and engagement in the classroom. But the report also pointed up issues with teacher preparation programs and the accessibility of sufficient resources. It is advised that future curriculum development put more of an emphasis on building teachers' capacities and provide resources that are in line with the requirements of the kids.